2009
DOI: 10.1029/2009gl039337
|View full text |Cite
|
Sign up to set email alerts
|

The 2009 L'Aquila earthquake (central Italy): A source mechanism and implications for seismic hazard

Abstract: We use InSAR and body‐wave seismology to determine independent source parameters for the 6th April 2009 Mw 6.3 L'Aquila earthquake and confirm that the earthquake ruptured a SW‐dipping normal fault with ∼0.6–0.8 m slip. The causative Paganica fault had been neglected relative to other nearby range‐frontal faults, partly because it has a subdued geomorphological expression in comparison with these faults. The L'Aquila earthquake occurred in an area with a marked seismic deficit relative to geodetically determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
156
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(175 citation statements)
references
References 20 publications
17
156
1
Order By: Relevance
“…This occurs not only because the Paganica ruptures correlate with well the focal mechanism and the epicenter locality (e.g. Chiarabba et al, 2009), but mainly due to the DInSAR analysis results (see also Atzori et al, 2009;Walters et al, 2009). In particular, the approximately 7 km long DIn-SAR predicted fault surface ruptures coincide with the surface ruptures observed in Paganica since they are only a couple of hundred meters up to 1 km apart (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This occurs not only because the Paganica ruptures correlate with well the focal mechanism and the epicenter locality (e.g. Chiarabba et al, 2009), but mainly due to the DInSAR analysis results (see also Atzori et al, 2009;Walters et al, 2009). In particular, the approximately 7 km long DIn-SAR predicted fault surface ruptures coincide with the surface ruptures observed in Paganica since they are only a couple of hundred meters up to 1 km apart (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The earthquake was assessed as a M W =6.2 or M L =5.8 (source INGV) or M W =6.3 (USGS), having a normal faulting mechanism of N147 • striking and dipping about 43 • towards the SW and a focal depth at 9 km. InSAR, body wave seismology and GPS data determined a SW∼50 • dipping normal fault with a maximum ∼0.6-0.9 m slip (Walters et al, 2009;Atzori et al, 2009;Anzidei et al, 2009). The epicenter was located a few km WSW from the city of L'Aquila which including the surrounding villages, hosts a population of about 100 000.…”
Section: Introductionmentioning
confidence: 99%
“…Notice that various methods show that the top of the activated fault is located from 3.0 km up to 0 km bellow from the Earths surface (Walters et al, 2009). The observed anomalies followed this temporal scheme: Two MHz electric anomalies appeared on 26 March 2009 and 2 April 2009 (Fig.…”
Section: Em Anomalies Observed Prior To the L'aquila Earthquakementioning
confidence: 99%
“…The strong (M w = 6.3) earthquake of 6 April 2009 in L'Aquila, Central Italy, occurred at 01:32:39 UTC and caused about 300 deaths and destruction in about 60 000 buildings of the area. The geometric and kinematic features and the source properties of the earthquake were studied by Atzori et al (2009), Cirella et al (2009 and Walters et al (2009). It has been shown that the earthquake rupture very possibly was associated with the Paganica normal fault which strikes NW-SE and dips SW (Fig.…”
Section: Introductionmentioning
confidence: 99%